2008
DOI: 10.1038/emboj.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

CENP-V is required for centromere organization, chromosome alignment and cytokinesis

Abstract: The mechanism of mitotic chromosome condensation is poorly understood, but even less is known about the mechanism of formation of the primary constriction, or centromere. A proteomic analysis of mitotic chromosome scaffolds led to the identification of CENP-V, a novel kinetochore protein related to a bacterial enzyme that detoxifies formaldehyde, a by-product of histone demethylation in eukaryotic cells. Overexpression of CENP-V leads to hypercondensation of pericentromeric heterochromatin, a phenotype that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 60 publications
4
43
3
1
Order By: Relevance
“…Here, its high expression in [ER−|PR−]HER2− tumors as compared with [ER−|PR−]HER2+ accords with our conception that metastasis is an easily gained property of triple negative cancers and suggests its importance in differentiating tumors of these two subtypes. CENPV is required for centromere organization, chromosome alignment and cytokinesis49, and CENPW plays crucial roles in the formation of a functional kinetochore involved in cell division during mitosis50. Over-expression of these two genes in [ER−|PR−]HER2− tumors suggests the crucial role of irregular cell cycle signaling in triple negative tumors that distinguish it from [ER−|PR−]HER2+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Here, its high expression in [ER−|PR−]HER2− tumors as compared with [ER−|PR−]HER2+ accords with our conception that metastasis is an easily gained property of triple negative cancers and suggests its importance in differentiating tumors of these two subtypes. CENPV is required for centromere organization, chromosome alignment and cytokinesis49, and CENPW plays crucial roles in the formation of a functional kinetochore involved in cell division during mitosis50. Over-expression of these two genes in [ER−|PR−]HER2− tumors suggests the crucial role of irregular cell cycle signaling in triple negative tumors that distinguish it from [ER−|PR−]HER2+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such sequences that are specific to centromeric constriction regions are expected to be of greater importance to centromere function because the centromeric constriction region is thought to play a central role in kinetochore formation and subsequent chromosome migration to the poles. 5,6 There are examples of satellite DNA that are specific to the centromeric constriction region and that are contained in all chromosomes of the host organisms. 7,8 To our knowledge, however, there is no example of such a sequence that is specific to the centromeric constriction region and that has undergone a rapid expansion to all chromosomes at the speciation level.…”
Section: Introductionmentioning
confidence: 99%
“…Those first two studies yielded rather modest lists comprising 62 and 79 proteins, respectively (Morrison et al 2002;Gassmann et al 2005). However, they did reveal that DNA topoisomerase II (Topo II) is phosphorylated by Aurora B kinase (Morrison et al 2002) and they also yielded the two interesting centromeric proteins Borealin and CENP-V (Gassmann et al 2005;Tadeu et al 2008). Later studies from the Fukui laboratory identified more than 200 proteins in isolated intact chromosomes from human cells (Uchiyama et al 2005;Takata et al 2007).…”
mentioning
confidence: 99%